2015
DOI: 10.18632/oncotarget.3199
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumour effects of antibodies targeting the extracellular cysteine-rich region of the receptor tyrosine kinase EphB4

Abstract: EphB4 is a membrane-bound receptor tyrosine kinase (RTK) commonly over-produced by many epithelial cancers but with low to no expression in most normal adult tissues. EphB4 over-production promotes ligand-independent signaling pathways that increase cancer cell viability and stimulate migration and invasion. Several studies have shown that normal ligand-dependent signaling is tumour suppressive and therefore novel therapeutics which block the tumour promoting ligand-independent signaling and/or stimulate tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…The first model, simulated a primitive endothelium using a HUVEC monolayer to investigate the invasiveness of 22Rv1 EphB4 over-expressing cells. Two rare, events were observed where HUVEC cells formed a circular enclosure around a 22Rv1 EphB4 over-expressing cell, and a similar event was also found for 22 Rv1 (2013) shows is that knockdown of EphB4 inhibits the invasiveness and migratory capability of tumour cells, which has been shown in multiple studies to date [16][17][118][119]135]. However, we show that CIL is restored not because the invasiveness of EphB4 overexpressing tumour cells has been suppressed, but that the interaction of with EphB4-Fc [242].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The first model, simulated a primitive endothelium using a HUVEC monolayer to investigate the invasiveness of 22Rv1 EphB4 over-expressing cells. Two rare, events were observed where HUVEC cells formed a circular enclosure around a 22Rv1 EphB4 over-expressing cell, and a similar event was also found for 22 Rv1 (2013) shows is that knockdown of EphB4 inhibits the invasiveness and migratory capability of tumour cells, which has been shown in multiple studies to date [16][17][118][119]135]. However, we show that CIL is restored not because the invasiveness of EphB4 overexpressing tumour cells has been suppressed, but that the interaction of with EphB4-Fc [242].…”
Section: Discussionsupporting
confidence: 60%
“…Studies have shown that the balance between EphB4 and ephrin-B2 is disrupted in many cancers [117,118]. In cancer, the normal balance is altered when EphB4 is over-expressed, disrupting the normal ligand-dependent signalling and instead activating pro-tumorigenic ligand-independent signalling [119]. A multitude of studies have reported that EphB4 is over-expressed in many epithelial cancers including, prostate (66% of cases) [118,120] [124][125][126], breast (58-64%) [127][128][129], endometrial (100%) [130], pancreatic (100%) [131], lung (100%) [18] and cervical cancer (95%) [132,133].…”
Section: Ephb4 Is a Promising Target For Metastatic Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Generation of 22Rv1 prostate cancer cells over-expressing EphB4 (22Rv1-B4) has been described previously [26]. Murine monoclonal antibodies specifically targeting amino acids 218 to 239 in the cysteine-rich region of the human EphB4 extracellular domain (PVAGSCVVDAVPAPGPSPSLYC) (mAb 11H4, mAb C1) were provided by BenEphex Biotechnologies Pty Ltd (Adelaide, Australia) [27]. The EphB4 specificity of these monoclonal antibodies is reflected in the data shown in Supplementary Fig.…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%